Diploid and tetraploid genomes of Acorus and the evolution of monocots - Liang Ma; Ke-Wei Liu; Zhen Li; Yu-Yun Hsiao; Yiying Qi; Tao Fu; Guang-Da Tang; Diyang Zhang; Wei-Hong Sun; Ding-Kun Liu; Yuanyuan Li; Gui-Zhen Chen; et al. (Nature Communications, 2023)
Abstract Monocots are a major taxon within flowering plants, have unique morphological traits, and show an extraordinary diversity in lifestyle. To improve our understanding of monocot origin and evolution, we generate chromosome-level reference genomes of the diploid Acorus gramineus and the tetraploid Ac. calamus, the only two accepted species from the family Acoraceae, which form a sister lineage to all other monocots. Comparing the genomes of Ac. gramineus and Ac. calamus, we suggest that Ac. gramineus is not a potential diploid progenitor of Ac. calamus, and Ac. calamus is an allotetraploid with two subgenomes A, and B, presenting asymmetric evolution and B subgenome dominance. Both the diploid genome of Ac. gramineus and the subgenomes A and B of Ac. calamus show clear evidence of whole-genome duplication (WGD), but Acoraceae does not seem to share an older WGD that is shared by most other monocots. We reconstruct an ancestral monocot karyotype and gene toolkit, and discuss scenarios that explain the complex history of the Acorus genome. Our analyses show that the ancestors of monocots exhibit mosaic genomic features, likely important for that appeared in early monocot evolution, providing fundamental insights into the origin, evolution, and diversification of monocots.